Assessment of Acute Nephronia and Renal Abscesses in Children: A Case from Quito, Ecuador - Adriana Arnao; Maria Augusta Guerrero; Nathaly Arias; Piedad Villacis; Katia Rivas; Mariana Flores; Jhoana Rivera; Jack Saltos; Gloria Soto; Jorge García; et al. (Current Practice in Medical Science Vol. 7, 2022)
The objective of this study is to publically speak about this pathology to avoid morbidity and mortality in children, due to the lack of national and international epidemiological data. Renal abscess and nephronia are uncommon childhood illnesses with uncertain global frequency. Nephronia is a condition that exists between pyelonephritis and renal abscess. Prompt diagnosis is critical for reducing morbidity and mortality (sepsis, renal injury, death). Although scientific advances have made these entities more visible, they may still remain undiagnosed. Nephronia and renal abscess must be considered in the differential diagnosis in all patients with persistent fever, abdominal pain, leukocytosis, elevated inflammation biomarkers and/or torpid clinical evolution. Patients with this condition need prolonged intravenous antibiotic therapy and may need surgery to treat them, typically when the lesions are larger than 3 to 5 cm and are accessible to percutaneous draining after intravenous antibiotic therapy alone fails. The study describe five cases of pediatric patients from four private hospitals in Quito, Ecuador followed during a one-year period. In each case, persistent fever, abdominal pain, severe leukocytosis, and/or increased inflammatory biomarkers were the main reasons the diagnosis was suspected. Only one of them had a history of urinary tract deformity, although another had a malformation that was discovered upon admission. Every instance was microbiologically isolated. They all made a full recovery. There have been no previous reports of these disorders in pediatric children in our nation, and there is little data worldwide.